Igre z mimezisom v poljski in slovenski prozi devetdesetih let - Tokarz, Bożena (Slavia Centralis, 2020)
Games with Mimesis in Polish and Slovene Prose of the ’90sGames with mimesis, present among the numerous trends and individual poetics in Polish and Slovene prose of the ’90s, define the model of receiving compositions and the model of their structure. They conduce to crossing borders between genres, cultures, borders in imagination, through making a field of a dialogue in the structure of a text. That field delivers other reading experiences than a closed story.
Keywords: mimesis; fiction; story; games; Polish and Slovene prose of the ’90s